Diklat Manasik Haji Bagi Guru Taman Pendidikan Al-Qur’an (TPQ) BKPAKSI Se-Kota Serang - Saepudin Saepudin; Sanin Sudrajat; Ahmad Mubarok; Munawarah Munawarah (Lembaga Pengembangan Kinerja Dosen, 2025)
This service activity discusses strengthening the fifth pillar of Islam, namely the Hajj. This service aims to increase the understanding, knowledge and competence of Al-Qur'an Education Park (TPQ) teachers at the Serang City Al-Qur'an Educator and Sakinah Family Coordinating Board (BKPAKSI) in Serang City regarding Hajj Manasik. This service methodology goes through a preliminary survey stage to find out the location that will be used as the location for the Hajj ritual training and training. then observe or carry out activities involving 25 TPQ teachers. This service activity was carried out at Wisma Haji (KBIHU) Mulyajati Cikole, Pandeglang Regency. The Hajj Manasik training for TPQ teachers went smoothly according to plan. Material and practice of Hajj rituals delivered by Hajj and Umrah supervisors from KBIHU Mulyajati. By implementing this practical training on Hajj rituals, the PkM team hopes that TPQ teachers as educators can transfer their knowledge of Hajj rituals to their students properly and correctly so that the students will love the Kaaba and the Prophet Muhammad more.